Second victim experience: cross-sectional survey at the Department of Maternal-Child Health in Udine. (30th September 2020) - Scarpis, E; Ruscio, E; Bianchet, B; Doimo, A; Moretti, V; Cocconi, R; Farneti, F; Castriotta, L; Quattrin, R
Abstract: Introduction: Healthcare workers (HCWs) can experience psychological distress if involved in adverse patient events, becoming second victims. The aim of this study is to determine the extension of the second victim phenomenon and the preference of the support resources of the HCWs working in the Department of Maternal and Child Health (DMC) at the Academic Hospital of Udine. Methods: A cross-sectional survey was carried out from June to November 2019. All HCWs involved in direct patient care working in the three units of DMC [Obstetrics and Gynaecology (OG), Neonatology (Neo), Pediatrics (Ped)] were included. A validated version in Italian language of the Second Victim Experience and Support Tool (SVEST) was used to assess the experience of second victim and the support resources preferred by the HCWs (Likert-scale: 1-5). Agreement of the support options were considered with an overall mean subscale score of ≥ 4.0. The Wilcoxon signed rank sum test was used to calculate the statistically significant differences (p < 0.01). Results: The response rate was 44, 9% (120/267). Women were 95.8%. Mean age was 38.7±9.7; HCWs from OG were 48.3%, 26.7% from Neo and 25% from Ped. Nurses were 34.2%, 32.5% were obstetrics, 15.8% were doctors and 8.3% were residents. HCWs who experienced adverse patient events were 80 (66.7%). Out of these, 63 (52.5%) were near-miss events. The overall mean score of the first two dimensions of SVEST ("Psychological distress" and "Physical distress", as representative of the trauma experience) was respectively 3.3±1.0 and 2.3±1.1. The difference between their scores was statistically significant (p < 0.01). The most preferred support option was: "a respected peer to discuss the details of what happened" with the 80.0%. Conclusions: The study highlights that HCWs of the DMC are frequently involved in adverse patient events. Psychological distress was significative more impactful than physical distress. The majority of HCWs preferred a peer for colleagues support. Key messages: SVEST is an instrument that helps to determine the support resources preferred by HCWs in order to develop a support program for second victim. A peer for colleagues support is the support resource preferred by the HCWs working in the Department of Maternal and Child Health.